Defect-free potassium manganese hexacyanoferrate cathode material for high-performance potassium-ion batteries - Leqing Deng (Nature Portfolio, 2021)
Potassium-ion battery is a promising candidate for post-Li-ion energy storage but the lack of cathode materials hinders practical exploitation. Here the authors investigate defect-free potassium manganese hexacyanoferrate as cathode active material for high energy and long lifespan K-based cells.